HUMAN-COMPUTER INTERACTION - Preece, Jenny, author 371664; Rogers, Yvonne, author 323668; Sharp, Helen, author 260174; Benyon, David, author 256975; Holland, Simon, author 338329; Carey, Tom, author 654741 (Wokingham, England : Addison-Wesley, 1995)
Offering the most comprehensive account of the multidisciplinary field of HCI, this book illustrates the powerful benefits of a user-oriented approach to the design of modern computer systems. It balances the technical and cognitive issues required for understanding the subtle interplay between people and computers, particularly in emerging fields like multimedia, virtual environments and computer supported cooperative work (CSCW). A unique feature is the inclusion of interviews with many leading authorities in HCI, providing personal insight into their work and conveying the excitement of current research activity: Deborah Hix, Roy Kalawsky, Marilyn Mantei, Tom Moran, Donald Norman, Brian Shackel, Ben Shneiderman, Bill Verplank, and Terry Winograd. Human-Computer Interaction is flexibly structured to allow a variety of learning paths for students in computer science, engineering, psychology and cognitive science. Programmers and system designers will appreciate its emphasis on the design of interactive systems.